2016
DOI: 10.1007/s11129-016-9176-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and semiparametric estimation of a finite horizon dynamic discrete choice model with a terminating action

Abstract: We study identi…cation and estimation of …nite-horizon dynamic discrete choice models with a terminal action. We …rst demonstrate a new set of conditions for the identi…cation of agents' time preferences. Then we prove conditions under which the per-period utilities are identi…ed for all actions in the agent's choice-set, without having to normalize the utility for one of the actions. Finally, we develop a computationally tractable semiparametric estimator. The estimator uses a two-step approach that does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 57 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…A terminal action ends the decision making process. Examples of terminal actions include a worker retiring (Rust and Phelan, 1997), a mortgage owner defaulting (Bajari, Chu, Nekipelov, and Park, 2016), and a household adopting a PV system (De Groote and Verboven, 2019). For both renewal and terminal actions, (6) simplifies to…”
Section: Eccp Equationsmentioning
confidence: 99%
“…A terminal action ends the decision making process. Examples of terminal actions include a worker retiring (Rust and Phelan, 1997), a mortgage owner defaulting (Bajari, Chu, Nekipelov, and Park, 2016), and a household adopting a PV system (De Groote and Verboven, 2019). For both renewal and terminal actions, (6) simplifies to…”
Section: Eccp Equationsmentioning
confidence: 99%
“…Rust (1994) showed that DDC models are not identified nonparametrically, and Magnac and Thesmar (2002) characterized the degree of underidentification. Important advances that followed include (but are not limited to) Heckman and Navarro (2007), Pesendorfer and Schmidt-Dengler (2008), Blevins (2014), Bajari, Chu, Nekipelov, and Park (2016), and Abbring and Daljord (2019). In terms of estimation, Rust (1987) introduced the nested fixed point maximum likelihood estimator in his seminal contribution, and Hotz and Miller (1993) pioneered a computationally convenient two-step estimator that was then further analyzed by a host of important studies (Hotz, Miller, Sanders, and Smith, 1994;Aguirregabiria andMira, 2002, 2007;Bajari, Benkard, and Levin, 2007;Pakes, Ostrovsky, and Berry, 2007;Pesendorfer and Schmidt-Dengler, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Rust (1994) showed that DDC models are not identified nonparametrically, and Magnac and Thesmar (2002) characterized the degree of underidentification. Important advances that followed include (but are not limited to) Heckman and Navarro (2007), Pesendorfer and Schmidt-Dengler (2008), Blevins (2014), Bajari, Chu, Nekipelov, and Park (2016), and Abbring and Daljord (2019). In terms of estimation, Rust (1987) introduced the nested fixed point maximum likelihood estimator in his seminal contribution, and Hotz and Miller (1993) pioneered a computationally convenient two-step estimator that was then further analyzed by a host of important studies (Hotz, Miller, Sanders, and Smith, 1994;Aguirregabiria andMira, 2002, 2007;Bajari, Benkard, and Levin, 2007;Pakes, Ostrovsky, and Berry, 2007;Pesendorfer and Schmidt-Dengler, 2008).…”
Section: Introductionmentioning
confidence: 99%